2017
DOI: 10.1080/10641963.2017.1339075
|View full text |Cite
|
Sign up to set email alerts
|

Acute glycemic and pressure responses of continuous and interval aerobic exercise in patients with type 2 diabetes

Abstract: Both continuous and interval aerobic exercise, in a same intensity, are effective for glycemic and pressure acute reductions in individuals with type 2 diabetes. For patients with greater risk of hypertension, we believe that the interval method is safer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…After the exercise sessions, they found that the interval exercise had better glycemic control results when compared to the continuous exercise. Santiago et al 3 conducted a training protocol similar to the one used in the present study and they also obtained satisfactory results: Glycemic levels were reduced both in the group of continuous training (45 mg/dL) and in the group of interval training (49 mg/dL). However, in these studies, the glycemic response to the exercise was assessed within the same moment and/or training status, which makes it difficult to establish a discussion with the proposal of the present study, which focused on the comparison between the glycemic responses at the beginning and at the end of an intervention.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…After the exercise sessions, they found that the interval exercise had better glycemic control results when compared to the continuous exercise. Santiago et al 3 conducted a training protocol similar to the one used in the present study and they also obtained satisfactory results: Glycemic levels were reduced both in the group of continuous training (45 mg/dL) and in the group of interval training (49 mg/dL). However, in these studies, the glycemic response to the exercise was assessed within the same moment and/or training status, which makes it difficult to establish a discussion with the proposal of the present study, which focused on the comparison between the glycemic responses at the beginning and at the end of an intervention.…”
Section: Discussionsupporting
confidence: 68%
“…Other studies 3,6,8 that analyzed the acute effect of aerobic exercise on the blood glucose of patients with T2D have also found glycemic reductions. Figueira et al 6 found a glycemic decrease of 27 mg/dL immediately after a 40-minute session with intensity of 70% of peak heart rate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years, discussion about physical training and type 2 diabetes, especially about endurance (aerobic and/or anaerobic) training has been common, aside from the type or modality of training. Currently, studies evaluating endurance training in patients with type 2 diabetes not only compare their effects with resistance and combined training effects, but also perform many comparisons between the different ways/models of endurance training ( Delevatti et al, 2016a ; Asano et al, 2017 ; Pandey et al, 2017 ; Santiago et al, 2018 ). These studies have been evaluating acute ( Terada et al, 2013 ; Delevatti et al, 2016b ; Asano et al, 2017 ; Santiago et al, 2018 ) and chronic ( Li et al, 2012 ; Ruffino et al, 2017 ; Pandey et al, 2017 ) effects in varying outcomes, including blood glucose, blood pressure, insulin, bradykinin, HbA1c, insulin resistance, and lipid profile.…”
Section: Introductionmentioning
confidence: 99%
“…Essa superioridade do treinamento intermitente também foi demonstrada por outros autores, que verificaram uma menor deposição de gordura, maior eficiência no metabolismo de glicose e uma melhora mais acentuada da biogênese mitocondrial (YOSHIOKA et al, 2001;POPOV et al, 2014;CHAVANELLE et al, 2017). Por outro lado, Santiago et al (2018) encontraram que ambos modelos de treinamento foram efetivos na regulação da glicemia e da pressão arterial; Sjoros et al 2018, que os dois modelos melhoraram a absorção de glicose e Motiani et al (2017) que o treinamento físico aeróbio contínuo foi mais efetivo na captação de glicose estimulada por insulina. O fato do nosso grupo apresentar níveis de glicemia e insulina dentro de valores relativamente normais diante dos achados em diabéticos, possa ser uma justificativa para não alteração dos dados referentes a ambos.…”
Section: Efeitos Do Treinamento Físico -Hormônios Sexuaisunclassified